Influência da tensão residual no empenamento de peças aeronáuticas usinadas a partir de placas laminadas de ligas de aluminio da serie 7XXX - Hyodo, Alexandre (Universidade Federal de São Carlos, 2002)
The fast growing of regional jets market has required from airframe manufacturers a prompt attending to market demands and the primary parts fabrication at a planned quality, quantity, and time at low costs. In order to achieve this, the process robustness is a key concept to be kept in mind, it means that the manufactured parts shall be conform to engineering specifications and geometric tolerances as well, regardless the raw material source used in machining process. Warping or machining distortion is one of the main problems identified during machining process. The corrective action for warping impacts the manufacturing lead-time, production costs, and production plan accomplishment. The influence of raw material on machining process performance is one of the main variables, is an assumption of this work. Recently, studies related to this approach have started and little technical literature is available. Otherwise, the availability of technical literature related to machining parameters, and cutting tools has been exhaustively explored. The aim of this work is to study the influence of material, in specific, the residual stress originated during thermo-mechanical processing of 7XXX series aluminum alloy plates, on warping of primary parts manufactured through milling machining. The layer removal method was the experimental technique chosen to measure the residual stress. Through this method is possible to determine the through thickness residual stress profile, the more suitable information for this study. In addition to this, the W parameter, which gives the average residual stress level per volume unit of plate and is a function of existing residual stress profile was also derived. It was correlated to warping level of machined from plates with several W parameter values. Parts machined from low W parameter values (lower than 1,0 kJ/m3) plates presented warping measurements remarkably lower than measurements made with parts machined from plates with W parameters values higher than 2,0 kJ/m3. This trend agrees with data available in literature and demonstrates the layer removal method results dependability, and its suitability to be applied for suppliers qualification purposes.
Keywords: Metalurgia; Tensões residuais; Ligas de alumínio; Usinagem; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA